O chão de fábrica das redes sociodigitais: o trabalho dos produtores de conteúdo na dinâmica do capitalismo contemporâneo - Cleverson Ramom Carvalho Silva (2023)
Influencers, content creators, tiktokers, YouTubers, videographers are just some of the many names used to refer to content-producing workers in recent media. They are on the cover of the magazine, on the TV show, in the soap opera and mainly on platforms like YouTube, Instagram and TikTok. They are responsible for the mass production of much of the content that we consume, share and interact with virtually. These workers work mainly on Sociodigital Networks (RSDs), a set of digital platforms that perform different functions and are part of the Communication Industry. Having as a guiding principle the maxim that the technical bases of work processes have been revolutionized according to the need of the valorization process itself, it is necessary to lay bare the material bases on which this industry is founded and which enables the existence of RSDs and the work intermediated by these platforms. This process engenders new possibilities for the subordination of living work, so that, in order to reveal the origin of the wealth that manifests itself in the billion-dollar profits of these corporations and the real functioning of the gears that move the mass production of content, it is necessary to achieve the objective proposed in this work: to analyze how and under what conditions the work of content producers, who work in Sociodigital Networks, is integrated into the capital reproduction cycle. This undertaking involves the challenge of debating the theories that populate the topic, mainly related to marketing and communication, and going behind the scenes of mass content production, visiting the factory floor, getting to know its workers. In an attempt to transpose the concrete reality into the thought reality, we made use of reports and documents of an audiovisual nature (documentaries, videos, photos and publications on websites) as well as an online questionnaire that included the participation of 307 workers producing content. With regard to unproductive work, the main results indicate that RSDs act as “advertising agencies”, with the particularity that they use algorithmic management mechanisms to sell advertisements, and only pay for content capable of attracting the audience. . In addition to activities related to advertising, the results also cover possibilities for productive work through the sale of content merchandise. With regard to working conditions and relationships, the main findings of this investigation point to an employment relationship, governed by unilaterally signed agreements, and subjection to guidelines and rules of conduct and remuneration linked to changeable and unclear criteria. Another result points to the strong role of intermediary agents, who deepen the commercial nature of these platforms, and to a working condition marked by insufficient wages, which makes these workers look for other sources of income, such as agreements signed directly with advertisers. , crowdfunding, tips and the sale of own products and services. In view of the above, we elaborate the following thesis: the significant technological improvement applied to the communication industry in recent decades engenders new forms of subordination of workers in the communication, creative and artistic areas; so that the RSDs employ this Work Force mostly in an unproductive way and, to a lesser extent, in a productive way, which ends up leading to a process already experienced by the working class as a whole: the precariousness of working conditions and relations as a response to the accumulation and expansion needs of the capitalist regime.